Method for preparing high-purity quartz through synergistic treatment of complexing impurity removal and preferential corrosion and product

Through the method of collaborative treatment of complexation and preferential dissolution, the problem of difficulty in removing impurities in quartz raw materials in the prior art is solved, and the efficient preparation of high-purity quartz is achieved, and the purity and quality of the product are improved.

CN119591112APending Publication Date: 2025-03-11江西有色地质矿产勘查开发院 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411758081.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

Smart Images

  • Figure CN119591112A_ABST
    Figure CN119591112A_ABST
Patent Text Reader

Abstract

The invention provides a high-purity quartz preparation method and product through complexing impurity removal and preferential corrosion co-processing, and the method comprises the following steps: carrying out sand making on quartz raw ore to obtain first quartz particles; performing pre-purification treatment on the first quartz particles to obtain second quartz particles; performing complexing impurity removal on the second quartz particles to obtain third quartz particles; carrying out flotation on the third quartz particles, and cleaning to obtain fourth quartz particles; and carrying out selective corrosion and tailing discarding on the fourth quartz particles, and filtering, washing and drying to obtain the high-purity quartz. According to the preparation method of the high-purity quartz, the requirement on the high-purity quartz raw material is relatively low, and the preparation of a product with higher purity under the same-quality raw material can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-purity mineral materials, and in particular to a method for preparing high-purity quartz by coordinated treatment of complexation and impurity removal and preferential dissolution, and a product thereof. Background Art

[0002] High-purity quartz refers to quartz sand with extremely high purity (SiO2 content of more than 99.9%) and still in a crystalline state. High-purity quartz is a mineral product made from crystal, vein quartz, granite pegmatite and other ores as raw materials and purified. It is the material basis for high-end products in the silicon industry and is widely used in strategic emerging industries. With the rapid development of new technology and new materials industries around the world, the demand for high-purity quartz continues to grow, especially in the fields of semiconductors, optical communications, and photovoltaics. According to the different SiO2 content, high-purity quartz can be divided into different grades.

[0003] At present, the preparation of high-purity quartz in China mainly relies on natural high-end crystal or high-quality vein quartz ore. Among them, the preparation of high-purity quartz from natural high-end crystal and high-quality vein quartz requires the raw materials to be purified and impurity-removed through calcination, water quenching, crushing, grinding, magnetic separation, flotation, acid leaching and other process flows to finally obtain high-purity quartz products. However, when high-purity quartz is prepared from quartz raw materials such as ordinary vein quartz ore, quartzite, quartz sandstone, granite pegmatite and natural quartz sand, there is often a problem in the process of simultaneously processing quartz particles of different qualities or even containing more impurities, which makes the average purity of the final product lower than the expected value, and it is impossible to prepare high-purity high-purity quartz products. At the same time, it is also difficult to remove lattice impurities in the quartz raw materials.

[0004] Based on the defects and shortcomings of the existing process, the present application uses two acid leaching and tailings removal to achieve high-purity preparation of low-quality quartz raw materials, which has relatively lower requirements for the quartz raw materials for preparing high-purity quartz, and can achieve the preparation of higher purity high-purity quartz with the same quality raw materials. Summary of the invention

[0005] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for preparing high-purity quartz by synergistic treatment of complexation and impurity removal and preferential dissolution; another purpose of the present invention is to provide a high-purity quartz product.

[0006] In order to achieve the above-mentioned purpose, the present invention provides, on one hand, a method for preparing high-purity quartz by coordinated treatment of complexation and impurity removal and preferential dissolution, the method comprising the following steps: sand making of quartz ore to obtain first quartz particles; pre-purifying the first quartz particles to obtain second quartz particles; complexation and impurity removal of the second quartz particles to obtain third quartz particles; flotation of the third quartz particles to obtain fourth quartz particles after washing; selectively dissolving and discarding the fourth quartz particles, filtering, washing and drying to obtain high-purity quartz.

[0007] Optionally, the quartz ore includes at least one of vein quartz, quartzite, quartz sandstone, granite pegmatite and natural sand; the sand making adopts any one or two or more of a jaw crusher, a cone crusher, a hammer crusher, a double-roll crusher, a ball mill and an autogenous mill in an arrangement and combination; the particle size of the first quartz particles is 40 to 100 meshes.

[0008] Optionally, the pre-purification treatment includes scrubbing and desludging the first quartz particles and magnetically separating and removing impurities.

[0009] Optionally, the scrubbing and desludging adopts mechanical scrubbing and desludging and / or ultrasonic desludging, and the desludging end point is that the solid content of the suspension in the scrubbing liquid is less than 1 g / L.

[0010] Wherein, the mechanical scrubbing and desludging includes desludging by using a hydrocyclone, a spiral classifier and a sand washer.

[0011] Optionally, the magnetic separation and impurity removal is performed using a magnetic separator with a magnetic field strength of more than 13000 Gs, the magnetic separation includes multiple stages of magnetic separation, and the end point of the magnetic separation is that the proportion of magnetic products is less than 0.1% of the mass of the input material.

[0012] Wherein, the magnetic separator includes one or more of a high gradient vertical ring magnetic separator and a wet high intensity magnetic separator.

[0013] Optionally, the complexing and impurity removal includes acid complexing and wet tailing removal, that is, firstly, a dynamic acid leaching reactor is used to perform mixed acid leaching on the second quartz particles, and then the complex produced during the mixed acid leaching process is discharged, the mixed acid includes 0.4-4.0 mol / L hydrofluoric acid, 0.5-2.0 mol / L oxalic acid, 0.6-4.8 mol / L hydrochloric acid and 0.8-6.4 mol / L nitric acid, the leaching time is 240-720 min, and the leaching temperature is 50-90°C.

[0014] Optionally, the method for discharging the complex is to use a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag to discharge the complex, and to discard the particles with a particle size below 150 mesh; the complex includes oxalic acid-based network floccules generated in the mixed acid reaction and the captured metal compounds and minerals containing metal ions.

[0015] Wherein, the second quartz particles are subjected to complexation and impurity removal, and in addition to obtaining the third quartz particles, the first tailings are also included.

[0016] Optionally, the flotation is to carry out reverse flotation in the pH range of 1.5 to 5.0 using one or more of hydrofluoric acid, hydrochloric acid and oxalic acid as adjusting agents, and one or more of dodecylamine, hexadecylamine and octadecylamine are used as collectors, and the amount of collector is 60 to 400 g / t; the washing is to wash the flotation concentrate with deionized water, and the washing end point is that the pH of the washing liquid is greater than 6.5.

[0017] Optionally, the selective dissolution is to carry out mixed acid leaching on the fourth quartz particles using a dynamic acid leaching reactor, wherein the mixed acid includes 0.8-4.0 mol / L hydrofluoric acid, 0.6-2.4 mol / L hydrochloric acid and 0.8-3.2 mol / L nitric acid, the leaching time is 480-960 min, and the leaching temperature is 50-90° C.

[0018] Optionally, the tailings are discarded by using a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag to remove mud, and the particles with a particle size below 200 mesh are discarded.

[0019] Optionally, the filtration is performed using one or more of a thickener, a vacuum filter, and a plate and frame filter press;

[0020] The washing is to repeatedly rinse the acid-leached quartz with deionized water until the pH of the filtrate is greater than 6.5;

[0021] The drying is carried out by one or more of freeze drying, vacuum drying or electrothermal drying.

[0022] Among them, the fourth quartz particles are selectively dissolved and discarded, and after filtering, washing and drying, in addition to high-purity quartz, a second tailing is also obtained; the minerals in the second tailing are mainly quartz containing impurities and some difficult-to-select silicate minerals, which are quartz products with relatively low purity and can be used as ordinary quartz sand or refined quartz sand.

[0023] Another aspect of the present invention provides a high-purity quartz product, which can be prepared by the above method.

[0024] The high-purity quartz product is characterized by a silicon dioxide content greater than 99.99%, which can reach more than 99.999% depending on the quality of the original ore.

[0025] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0026] (1) The present invention can realize the formation of complexes of some difficult-to-select impurities through complexation and remove them by physical methods. At the same time, it can realize the preferential dissolution of silicate gangue minerals, thereby reducing their particle size, increasing their specific surface area, and improving their floatability, so that their subsequent flotation process has more excellent selectivity, which can effectively improve the separation and purification effects.

[0027] (2) The present invention can achieve directional corrosion of unstable weak sites containing impurities in quartz grains through selective dissolution and tailing of impurity minerals. On the one hand, the parts of the quartz particles containing impurities are preferentially dissolved to expose and remove the impurities. On the other hand, the quartz grains containing more impurities are dissolved and refined and removed in the tailing process, thereby effectively improving the purification effect of the quartz sample and obtaining a higher purity high-purity quartz product.

[0028] (3) The high-purity quartz preparation method of the present invention has relatively lower requirements for high-purity quartz raw materials, and can achieve the preparation of higher-purity high-purity quartz products with the same quality of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and other objects and / or features of the present invention will become more apparent through the following description in conjunction with the accompanying drawings, in which:

[0030] Figure 1 The electron microscope photo of the tailings morphology after the complexation and impurity removal by the method of the present invention is shown;

[0031] Figure 2 An electron microscope photograph showing the morphology of the tailings after selective dissolution by the method of the present invention;

[0032] Figure 3 An electron microscope photograph of high-purity quartz prepared by the present invention is shown. DETAILED DESCRIPTION

[0033] Hereinafter, the method for preparing high-purity quartz and the product thereof by coordinated treatment of complexation and impurity removal and preferential dissolution of the present invention will be described in detail in conjunction with exemplary embodiments.

[0034] Exemplary Embodiment 1

[0035] This exemplary embodiment provides a method for preparing high-purity quartz by coordinated treatment of complexation and impurity removal and preferential dissolution.

[0036] The preparation method may include the following steps:

[0037] S1. Making sand from quartz ore to obtain first quartz particles.

[0038] In this embodiment, the quartz ore includes vein quartz, quartzite, quartz sandstone, granite pegmatite and natural sand.

[0039] In this embodiment, the sand making adopts any one or two or more of a jaw crusher, a cone crusher, a hammer crusher, a roll crusher, a ball mill and an autogenous mill in an arranged combination; a screen is set at the discharge port of the mill used to obtain the first quartz particles with a particle size of 40 to 100 mesh, such as 40 mesh, 60 mesh, 70 mesh, 100 mesh, etc.

[0040] Among them, selecting the particle size of the first quartz particles to be 40-100 meshes can ensure that the gangue minerals in the quartz ore are basically dissociated or exposed on the particle surface, which is easy to remove later. Selecting a particle size of not less than 100 meshes can avoid the problem that the quartz particles are too fine, causing the target mineral quartz to flow out with the tailings during scrubbing and acid leaching, thereby reducing the yield of high-purity quartz.

[0041] S2. Pre-purify the first quartz particles to obtain second quartz particles.

[0042] In this embodiment, the pre-purification treatment includes scrubbing and desludging the first quartz particles and magnetically separating and removing impurities.

[0043] In this embodiment, the scrubbing and desludging adopts mechanical scrubbing and desludging and / or ultrasonic desludging, and the desludging end point is that the solid content of the suspension in the scrubbing liquid is less than 1 g / L.

[0044] Wherein, the mechanical scrubbing and desludging includes desludging by using a hydrocyclone, a spiral classifier and a sand washer.

[0045] In this embodiment, the purpose of scrubbing and desludging is to remove clay minerals and weathered mineral dust that are dissociated or exposed in the sand making process. At the same time, mechanical force or ultrasonic force can be used to further improve the monomer dissociation degree of the particles, and the gangue minerals with lower hardness or larger embedded particle size can be discharged with the scrubbing liquid.

[0046] Among them, the advantage of selecting the desludging end point as the suspended liquid solid content in the scrubbing liquid being less than 1g / L is that the carrying capacity of the scrubbing liquid for clay minerals and fine dust can be utilized to remove the clay minerals and fine dust therein as much as possible, thereby avoiding affecting the subsequent purification process effect.

[0047] In this embodiment, the magnetic separation and impurity removal is performed using a magnetic separator with a magnetic field strength of more than 13000 Gs; the magnetic separator includes one or more of a high gradient vertical ring magnetic separator and a wet high intensity magnetic separator.

[0048] In this embodiment, the advantage of selecting a magnetic separator with a magnetic field strength of more than 13000Gs is that it can remove weakly magnetic gangue minerals such as tourmaline and limonite mica that are difficult to separate by conventional processes in the second quartz particles; the reason for selecting a superconducting magnetic separator, a high gradient vertical ring magnetic separator or a wet high-intensity magnetic separator is that the magnetic separation effects of these three magnetic separators are relatively good, and the separation of weakly magnetic minerals can be better achieved.

[0049] In this embodiment, the magnetic separation includes multi-stage magnetic separation, and the end point of the magnetic separation is that the proportion of magnetic products is less than 0.1% of the mass of the input material.

[0050] Among them, the use of multi-stage magnetic separation can avoid the inability of a single magnetic separation to separate the main weakly magnetic gangue minerals; when the proportion of magnetic products after magnetic separation is less than 0.1% of the feed mass, it can be considered that the magnetic minerals have been basically separated and removed.

[0051] S3, the second quartz particles are subjected to complexation and impurity removal to obtain third quartz particles.

[0052] In this embodiment, the complexing and impurity removal includes acid complexing and wet tailing removal, that is, firstly, a dynamic acid leaching reactor is used to perform mixed acid leaching on the second quartz particles, and then the complex generated during the mixed acid leaching process is discharged.

[0053] In this embodiment, the mixed acid includes 0.4-4.0 mol / L hydrofluoric acid, such as 0.4 mol / L, 0.7 mol / L, 1.5 mol / L, 2.0 mol / L, 2.6 mol / L, 3.9 mol / L, etc.; 0.5-2.0 mol / L oxalic acid, such as 0.5 mol / L, 0.7 mol / L, 1.0 mol / L, 1.5 mol / L, 1.9 mol / L, etc.; 0.6-4.8 mol / L hydrochloric acid, such as 0.6 mol / L, 0.9 mol / L, 1.5 mol / L, 2.0 mol / L, 3.5 mol / L, 4.8 mol / L, etc.; 0.8-6.4 mol / L nitric acid, such as 0.8 mol / L, 1.5 mol / L, 2.8 mol / L, 3.0 mol / L, 4.5 mol / L, 6.4 mol / L, etc.

[0054] The purpose of selecting 0.4-4.0 mol / L hydrofluoric acid is to utilize the difference in the dissolution rate of quartz and silicate minerals by hydrofluoric acid under mixed acid conditions to preferentially dissolve the gangue minerals in the second quartz particles, so that the gangue minerals are preferentially pulverized, which is convenient for removal in tailings and subsequent flotation.

[0055] The purpose of selecting 0.5-2.0 mol / L oxalic acid is to utilize the precipitation and complexation between oxalic acid and dissolved metal ions and gangue mineral powder to aggregate them, making them easier to remove in tailings and subsequent flotation.

[0056] The purpose of selecting 0.6-4.8 mol / L hydrochloric acid and 0.8-6.4 mol / L nitric acid is to utilize their synergistic mechanism to further increase the solubility of impurities and enhance the effect of hydrofluoric acid.

[0057] In this embodiment, the acid leaching time is 240 to 720 min, such as 240 min, 270 min, 300 min, 450 min, 520 min, 600 min, 700 min, etc.; the acid leaching temperature is 50 to 90°C, such as 50°C, 55°C, 62°C, 75°C, 88°C, etc.

[0058] The purpose of selecting the above-mentioned acid leaching time and acid leaching temperature is to ensure that the differential dissolution of gangue minerals and quartz can be fully carried out during the acid leaching process, while ensuring the role of conventional acid leaching in removing metal elements.

[0059] In this embodiment, the method for discharging the complex is to use a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag to discharge the complex, and to discard the particles with a particle size below 150 mesh; the complex includes oxalic acid-based network floccules generated in the mixed acid reaction and the captured metal compounds and minerals containing metal ions.

[0060] The purpose of selecting the above equipment is to use hydraulic action to more efficiently remove powdered impurities in quartz particles, while also playing a scrubbing role to separate impurity particles that are adhered to the quartz particles.

[0061] In this embodiment, the second quartz particles are subjected to complexation and impurity removal, and in addition to obtaining the third quartz particles, the first tailings are also obtained.

[0062] Among them, the main components of the first tailings are silicate minerals, and fine-grained clay and some granular aggregates precipitated by oxalic acid complexation can be seen. Figure 1 The electron microscope photograph of the first tailings morphology obtained after wet tailings disposal according to the method of the present invention is shown. The figure shows the complexing effect of oxalic acid on the gangue minerals.

[0063] S4, flotation is performed on the third quartz particles, and fourth quartz particles are obtained after washing.

[0064] In this embodiment, the flotation is reverse flotation performed at a pH range of 1.5 to 5.0 using one or more of hydrofluoric acid, hydrochloric acid and oxalic acid as an adjusting agent.

[0065] Among them, the purpose of selecting the above-mentioned as the adjusting agent is to inhibit quartz and further improve the flotation separation efficiency; reverse flotation at a pH of 1.5 to 5.0 can make the quartz particles and other gangue minerals have opposite surface potentials, ensuring the collection effect of the cationic collector.

[0066] In this embodiment, one or more of dodecylamine, hexadecylamine and octadecylamine are used as collectors, and the amount of collector is 60-400 g / t, such as 60 g / t, 100 g / t, 120 g / t, 250 g / t, 300 g / t, 390 g / t, etc.; the washing is to wash the flotation concentrate with deionized water, and the washing end point is that the pH of the washing liquid is greater than 6.5.

[0067] Among them, the purpose of selecting dodecylamine, hexadecylamine or octadecylamine as collectors is that cationic collectors can achieve targeted capture of gangue minerals, combine with the surface of gangue minerals, make them hydrophobic, and float out with foam; the purpose of selecting the collector dosage of 60 to 400 g / t is that this concentration range can ensure the capture effect while avoiding excessively high agent concentration to increase costs.

[0068] S5. The fourth quartz particles are selectively dissolved and discarded, and high-purity quartz is obtained through filtering, washing and drying.

[0069] In this embodiment, the selective dissolution is to perform mixed acid leaching on the fourth quartz particles using a dynamic acid leaching reactor, and the mixed acid includes 0.8-4.0 mol / L hydrofluoric acid, such as 0.8 mol / L, 1.2 mol / L, 1.7 mol / L, 2.1 mol / L, 2.6 mol / L, 3.9 mol / L, etc.; 0.6-2.4 mol / L hydrochloric acid, such as 0.6 mol / L, 1.1 mol / L, 1.5 mol / L, 1.9 mol / L, 2.3 mol / L, etc.; 0.8-3.2 mol / L nitric acid, such as 0.8 mol / L, 1.2 mol / L, 1.5 mol / L, 2.3 mol / L, 2.7 mol / L, 3.1 mol / L, etc.

[0070] The purpose of selecting 0.8 to 4.0 mol / L of hydrofluoric acid is that when hydrofluoric acid is used to dissolve quartz, it will preferentially dissolve the internal defects or the internal impurity concentrated areas, so that the quartz with a higher impurity content in the fifth quartz grains will be preferentially dissolved, so that it will be directly dissolved or pulverized into quartz grains with relatively smaller particle size after dissolution, which is convenient for removal in the tailing.

[0071] The main purpose of selecting 0.6-2.4 mol / L hydrochloric acid and 0.8-3.2 mol / L nitric acid is to utilize their synergistic mechanism to further increase the solubility of impurities and also to enhance the effect of hydrofluoric acid.

[0072] In this embodiment, the acid leaching time is 480-960 min, such as 480 min, 570 min, 600 min, 750 min, 820 min, 910 min, 950 min, etc.; the acid leaching temperature is 50-90°C, such as 50°C, 55°C, 62°C, 76°C, 89°C, etc.

[0073] The purpose of selecting the above-mentioned acid leaching time and acid leaching temperature is to further improve the reaction degree of acid leaching, to avoid the reaction time being too short, the reaction temperature being too low, and the static acid leaching failing to achieve uniform pulverization of impurity particles in quartz, thus affecting the separation effect.

[0074] In this embodiment, the tailings are discarded by using a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag to remove mud, and the particles with a particle size less than 200 mesh are discarded.

[0075] The purpose of selecting the above equipment is to use hydraulic action to more efficiently remove powdered impurities in quartz particles, and at the same time play a scrubbing role to separate impurity particles that are adhered to the quartz particles.

[0076] In this embodiment, the fourth quartz particles are selectively dissolved and tailings are discarded. After filtering, washing and drying, in addition to obtaining high-purity quartz particles, the second tailings are also obtained.

[0077] Among them, the minerals in the second tailings are mainly quartz, which is a quartz product with relatively low purity and can be used as ordinary quartz sand or refined quartz sand. Figure 2 The electron microscope photograph of the second tailings morphology obtained by selective dissolution and tailings discarding according to the method of the present invention is shown. From the figure, it can be seen that hydrofluoric acid has a preferential dissolution effect on weak sites of quartz.

[0078] In this embodiment, the filtration is performed by using one or more of a thickener, a vacuum filter, and a plate and frame filter press.

[0079] The purpose of selecting the above equipment for filtering is to remove excess water from the quartz particles, reduce their water content, discharge the acid introduced during the acid leaching process, and reduce the water consumption during the cleaning process.

[0080] In this embodiment, the washing is to use deionized water to repeatedly rinse the acid-leached quartz until the pH of the filtrate is greater than 6.5.

[0081] The purpose of this step is to remove the acid solution introduced during the acid leaching process and to discharge the ionic salts dissolved in the acid solution to avoid affecting the purity of the final product.

[0082] In this embodiment, the drying is performed by one or more of freeze drying, vacuum drying or electrothermal drying.

[0083] The purpose of drying is to remove free water in the final product and to avoid the quartz particles from adsorbing hydroxyl groups due to incomplete drying, which would affect subsequent use.

[0084] Exemplary Embodiment 2

[0085] This exemplary embodiment provides a high-purity quartz product, which can be prepared by the method described in exemplary embodiment 1.

[0086] In this embodiment, the high-purity quartz product is characterized by a silicon dioxide content greater than 99.99%, which can reach more than 99.999% depending on the quality of the original ore. Figure 3 Shown is an electron microscope photograph of high-purity quartz prepared by the method of the present invention.

[0087] In order to better understand the above exemplary embodiments of the present invention, they are further described below with reference to specific examples.

[0088] Example 1

[0089] The sample raw material is granite pegmatite, and the mineral composition is 52% plagioclase, 20% potassium feldspar, 23% quartz, 4% tourmaline, and 1% garnet. It is a difficult-to-select quartz raw material.

[0090] The chemical composition is shown in Table 1:

[0091] Table 1 Analysis results of constant chemical components of samples

[0092]

[0093] The preparation method comprises the following steps:

[0094] Step 1: Use a jaw crusher and a ball mill to make sand from the quartz ore, set a screen at the discharge port of the mill used, and obtain the first quartz particles with a particle size of 40 to 100 meshes.

[0095] Step 2: The first quartz particles are scrubbed and deslimed by ultrasonic desliming, the suspension on the upper part of the ultrasonic container is poured out, and clarified scrubbing liquid is added until the solid content of the suspension in the scrubbing liquid is less than 1g / L, and the scrubbed concentrate is magnetically separated and impurities are removed by a wet high-intensity magnetic separator with a magnetic field strength of 23000Gs. The magnetic separation is a two-stage magnetic separation to obtain the second quartz particles.

[0096] Step 3: The second quartz particles are subjected to complexation and impurity removal in a water bath shaker, wherein the mixed acid ratio is 0.4 mol / L hydrofluoric acid, 2.0 mol / L oxalic acid, 0.8 mol / L hydrochloric acid, and 1.4 mol / L nitric acid, the acid leaching time is 240 min, and the acid leaching temperature is 90°C. The particles are then discarded and desludged using an ultrasonic cleaning machine with a nylon filter bag, and the particles with a particle size less than 150 mesh are discarded to obtain third quartz particles.

[0097] Step 4: using hydrofluoric acid as a regulator to reverse float the third quartz particles at a pH of 3.0, using dodecylamine as a collector, the amount of the collector is 120 g / t, and washing the flotation concentrate with deionized water. The washing end point is that the pH of the washing liquid is greater than 6.5, and washing obtains the fourth quartz particles.

[0098] Step 5: The fourth quartz particle is selectively dissolved and tailing is discarded in a dynamic acid leaching reactor, the mixed acid ratio is 0.8 mol / L hydrofluoric acid, 1.2 mol / L hydrochloric acid, 1.4 mol / L nitric acid, the acid leaching time is 480 min, the acid leaching temperature is 90°C, and then the ultrasonic cleaning machine with a filter bag is used for desludging, and the particles with a particle size less than 200 mesh are wet-discarded, and high-purity quartz is obtained after filtering, washing and drying.

[0099] The obtained high-purity quartz was analyzed for impurity content with reference to the national standard GB / T3284-2015, and the total amount of 17 impurity elements was 41.5ppm, which was 4N5 grade high-purity quartz sand.

[0100] Example 2

[0101] The sample raw material is granite pegmatite powder, and the mineral components are microcline, albite, quartz, garnet, and rutile, which are difficult-to-select quartz raw materials.

[0102] The chemical composition is shown in Table 2:

[0103] Table 2 Analysis results of sample constant chemical composition

[0104]

[0105] The preparation method comprises the following steps:

[0106] Step 1: Use a ball mill to make sand from the quartz ore, and set a screen at the discharge port of the mill to obtain the first quartz particles with a particle size of 40 to 100 meshes.

[0107] Step 2: Use a sand washer to scrub and desludging the first quartz particles, discharge the suspension, and add clarified scrubbing liquid until the solid content of the suspension in the scrubbing liquid is less than 1g / L. Use a wet high-intensity magnetic separator with a magnetic field strength of 13000Gs to magnetically separate and remove impurities from the scrubbed concentrate. The magnetic separation is a two-stage magnetic separation to obtain the second quartz particles.

[0108] Step 3: The second quartz particles are subjected to complexation and impurity removal in a water bath shaker, the mixed acid ratio is 2.0 mol / L hydrofluoric acid, 2.0 mol / L oxalic acid, 1.6 mol / L hydrochloric acid, 2.0 mol / L nitric acid, the acid leaching time is 300 min, the acid leaching temperature is 60°C, and then the tailing is discarded, the sand washer is used for desludging, and the particles with a particle size less than 150 mesh are discarded with a nylon screen to obtain the third quartz particles.

[0109] Step 4: using hydrofluoric acid as a regulator to reverse float the third quartz particles at a pH of 2.5, using octadecylamine as a collector, the amount of the collector is 100 g / t, and washing the flotation concentrate with deionized water. The washing end point is that the pH of the washing liquid is greater than 6.5, to obtain fourth quartz particles.

[0110] Step 5: The fourth quartz particle is selectively dissolved and tailing is discarded in a dynamic acid leaching reactor, the mixed acid ratio is 0.4 mol / L hydrofluoric acid, 1.2 mol / L hydrochloric acid, 1.4 mol / L nitric acid, the acid leaching time is 480 min, the acid leaching temperature is 90°C, and then an ultrasonic cleaning machine with a filter bag is used for desludging, a sand washing machine is used for desludging, and a nylon screen is used for wet tailing of particles with a particle size less than 200 meshes, and high-purity quartz is obtained by filtering, washing and drying.

[0111] The obtained high-purity quartz was analyzed for impurity content with reference to the national standard GB / T3284-2015, and the total amount of 17 impurity elements was 19.25ppm, which was 4N8 grade high-purity quartz sand.

[0112] Although the present invention has been described above in conjunction with the exemplary embodiments and the accompanying drawings, it should be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.

Claims

1. A method for preparing high-purity quartz by synergistic treatment of complexation and impurity removal and preferential dissolution, characterized in that: The method comprises the following steps: 1) Making sand from quartz ore to obtain first quartz particles; 2) performing a pre-purification treatment on the first quartz particles to obtain second quartz particles; 3) performing complexation and impurity removal on the second quartz particles to obtain third quartz particles; 4) flotating the third quartz particles and washing them to obtain fourth quartz particles; 5) The fourth quartz particles are selectively dissolved and discarded, and high-purity quartz is obtained through filtering, washing and drying.

2. The method for preparing high-purity quartz according to claim 1, characterized in that: The quartz ore includes at least one of vein quartz, quartzite, quartz sandstone, granite pegmatite and natural sand; the sand making adopts any one or two or more of a jaw crusher, a cone crusher, a hammer crusher, a double-roll crusher, a ball mill and an autogenous mill in an arranged combination; the particle size of the first quartz particles is 40 to 100 meshes.

3. The method for preparing high-purity quartz according to claim 1, characterized in that: The pre-purification treatment in step 2) includes scrubbing and desludging the first quartz particles and magnetically separating and removing impurities.

4. The method for preparing high-purity quartz according to claim 3, characterized in that: The scrubbing and desludging adopts mechanical scrubbing and desludging and / or ultrasonic desludging, and the desludging endpoint is that the solid content of the suspension in the scrubbing liquid is less than 1g / L. The magnetic separation and impurity removal uses a magnetic separator with a magnetic field strength of more than 13000Gs for magnetic separation, and the magnetic separation includes multi-stage magnetic separation. The magnetic separation endpoint is that the proportion of magnetic products is less than 0.1% of the feed mass.

5. The method for preparing high-purity quartz according to claim 1, characterized in that: The complexing and impurity removal in step 3) includes acid complexing and wet tailing removal, that is, firstly, a dynamic acid leaching reactor is used to carry out mixed acid leaching on the second quartz particles, and then the complex generated during the mixed acid leaching process is discharged, wherein the mixed acid comprises 0.4-4.0 mol / L hydrofluoric acid, 0.5-2.0 mol / L oxalic acid, 0.6-4.8 mol / L hydrochloric acid and 0.8-6.4 mol / L nitric acid, the leaching time is 240-720 min, and the leaching temperature is 50-90° C.; The method for discharging the complex is to use a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag to discharge the complex, and to discard the particles with a particle size less than 150 mesh; the complex includes an oxalic acid-based network flocculent generated in a mixed acid reaction and the captured metal compounds and minerals containing metal ions.

6. The method for preparing high-purity quartz according to claim 1, characterized in that: In step 4), the flotation is reverse flotation at a pH range of 1.5 to 5.0 using one or more of hydrofluoric acid, hydrochloric acid and oxalic acid as an adjusting agent, and one or more of dodecylamine, hexadecylamine and octadecylamine are used as collectors, with the amount of collector being 60 to 400 g / t; the washing is washing the flotation concentrate with deionized water, and the washing end point is that the pH of the washing liquid is greater than 6.

5.

7. The method for preparing high-purity quartz according to claim 1, characterized in that: The selective dissolution in step 5) is to carry out mixed acid leaching on the fourth quartz particles using a dynamic acid leaching reactor, wherein the mixed acid includes 0.8-4.0 mol / L hydrofluoric acid, 0.6-2.4 mol / L hydrochloric acid and 0.8-3.2 mol / L nitric acid, the leaching time is 480-960 min, and the leaching temperature is 50-90° C.

8. The method for preparing high-purity quartz according to claim 1, characterized in that: The tailings discarded in step 5) are desludging by using a hydrocyclone, a spiral classifier, a sand washer, a centrifuge or an ultrasonic cleaning machine with a filter bag, and the particles with a particle size below 200 mesh are discarded.

9. The method for preparing high-purity quartz according to claim 1, characterized in that: The filtration in step 5) is performed by using one or more of a thickener, a vacuum filter, and a plate and frame filter press; The washing is to repeatedly rinse the acid-leached quartz with deionized water until the pH of the filtrate is greater than 6.5; The drying is carried out by one or more of freeze drying, vacuum drying or electrothermal drying.

10. A high purity quartz product, characterized in that: The high-purity quartz product is prepared by the method described in any one of claims 1 to 9, and the high-purity quartz product is characterized by a silicon dioxide content greater than 99.99%, which can reach more than 99.999% depending on the quality of the original ore.

Citation Information

Cited By

  • Washing method of high-purity ammonium metavanadate

    CN121085318A